PENGARUH AKTUALISASI DIRI DAN PENEMPATAN TERHADAP MOTIVASI PEGAWAI PT. PERKEBUNAN NUSANTARA III MEDAN - Yusrita Pulungan; Abdul Naim Manurung (JRMB (Jurnal Riset Manajemen & Bisnis), 2018)
The ability of company in maximizing human resources will have an impact on increasing employee motivation in working. Work motivation is a willingness to achieve organizational goals that are influenced by the ability of the business to satisfy some individual needs or a psychological process that takes place in the interaction between different personalities-different to meet the needs as a human. This process produces a drive of willpower and a desire to act through decisions. The formulation of this research problem is the influence of Self Actualization and Employee Placement, either partially or simultaneously to the Motivation Employees in PT. Perkebunan Nusantara III (Persero) Medan. The population of this study is all employees who work in the company. The samples taken in this study were 86 people. Data were collected using observations and questionnaires. The data were tested by using the validity and reliability test. Furthermore, the data were analyzed by using multiple regression analysis, ujit t, F test, and coefficient of determination. This study concludes that based on partial and simultaneous test results, self actualization and employee placement affect the motivation. The ability of self-actualization and employee placement in explaining motivation is 93.3% while the rest of 6.7% is explained by other factors not included in this research model.